THE INFLUENCE OF PRICE AND SERVICE QUALITY ON THE DECISION TO PURCHASE OF REFERENCE BOOKS IN STUDENTS OF ECONOMICS EDUCATION PROGRAM 2020-2021 - Raulia Ade Maulida; Sudarman Sudarman; Sutrisno Sutrisno (Faculty of Teacher Training and Education, Mulawarman University, 2022)
Students as consumers will be faced with the many choices of reference books needed, so students must be able to decide on purchasing reference books according to their needs. During the process of making a purchase decision, students are influenced by prices and also the quality of bookstore services . This study aims to find out how price and service quality influence the decision to purchase reference books in bookstores for students of the economics education study program class of 2020-2021. In measuring a sample researchers used a purposive method sampling is taking samples with certain considerations. Data collection was carried out by distributing questionnaires to 129 economic education students. The approach used in this research is a quantitative approach. To test the validity of the data researchers used validity and reliability tests. The data analysis technique used in this research is multiple regression test (partial test with T-test and simultaneous test with f-test) and model test with coefficient of determination (R2) assisted with SPSS statistics 16 software. The hypothesis results of this study indicate that price and service quality have a significant and positive effect on the decision to purchase reference books in bookstores for students of the economics education study program class of 2020-2021.